ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI DI BURSA EFEK INDONESIA - Setiawati, Setiawati (Jurnal Daya Saing, 2018)
This study aims to analyze and assess the financial performance of the pharmaceutical sector manufacturing companies on the Indonesia Stock Exchange in the 2015-2017 period based on liquidity ratios, activity ratios, profitability ratios, and solvency ratios. This type of research uses quantitative research. This study uses secondary data in the form of company financial statements and the determination of samples using purposive sampling technique. The analysis method used in this research is financial ratio analysis. The results of the study based on the overall financial ratios both based on liquidity ratios, activity ratios, profitability ratios and solvency ratios indicate that the Sido Muncul Herbal Medicine and Pharmacy Industry has the best financial performance compared to other pharmaceutical sector manufacturing companies. Keywords: Financial Performance Analysis, Ratio Analysis